2013
DOI: 10.4028/www.scientific.net/amm.393.102
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Thickness and Fabric for Sound Absorption of Biopolymer Composite

Abstract: Biopolymer foam was prepared by the reaction of bio-monomer based on vegetable oil with commercial Polymethane Polyphenyl Isocyanate (Modified Polymeric-MDI). The acoustic study of biopolymer foam was examined by impedance tube test according to the ASTM E-1050 and laminated with three types of textile such as polyester, cotton and single knitted jersey. It was revealed that the thicker the fabric the higher the sound absorption coefficient (α) at medium frequency level. The higher the number of layers or thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…A previous study reported that the sound absorption rate of soundproofing materials differs according to the state of attachment [19][20][21]. It also depends on the conditions of the backside of the material (the presence/absence of a back wall of the material, the characteristics of the wall, the presence of an air layer between the material and the wall, the thickness of the air layer, etc.)…”
Section: Application and Results Of The Noise Reduction Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study reported that the sound absorption rate of soundproofing materials differs according to the state of attachment [19][20][21]. It also depends on the conditions of the backside of the material (the presence/absence of a back wall of the material, the characteristics of the wall, the presence of an air layer between the material and the wall, the thickness of the air layer, etc.)…”
Section: Application and Results Of The Noise Reduction Methodsmentioning
confidence: 99%
“…Various types of soundproofing materials were tested for their noise-proofing performances. Furthermore, the sound absorption efficiency of soundproofing material varies depending on the setting, including the presence of a wall, the thickness of air layer, and the material attachment [19][20][21]. Therefore, it is critical that the soundproofing material is sparingly used in optimal spots rather than over large areas to minimize overheating, space usage, and weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, scholars have impregnated graphene oxide into PU foam to strengthen its porosity and tortuosity to improve sound absorption coefficient . Hassan et al laminated biopolymer foam, cotton fabric, and knitted fabric to enhance sound absorption at medium frequencies . Kraitape et al found that the incorporation of recycled PU foam polyol decreased the cavity size and yielded a wider cells distribution, which strengthened the tensile and compressive properties .…”
Section: Introductionmentioning
confidence: 99%
“…The attention on natural biomass feedstock is also on the conversion process into monomer, polymers, and composites. Several works have also been investigated with respect to the production of polyols for the PU industry which included the acid liquefaction of identified biomass residues [6,1,11].…”
Section: Introductionmentioning
confidence: 99%